Repurposing an old drug for a new use: glybenclamide exerts antiplatelet activity by interacting with the thromboxane A2 receptor - Ting Harold J; Murray Wallace J; Khasawneh Fadi T (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the potential antagonistic activity of the antidiabetic agent glybenclamide for the human platelet thromboxane A2 receptor (abbreviated as TPR). Methods: Platelets were obtained from healthy donors. Aggregation studies were performed in a model 700 aggregometry system. Radioactivity was counted in a Beckman LS 6000 liquid scintillation counter and calcium imaging was performed using an LS50B PerkinElmer Fluorescence Spectrometer. Results: It was found that glybenclamide: 1) inhibited aggregation induced by the TPR agonist U46619 (IC50=2.3±0.31 μmol/L) and by the thromboxane A2 precursor arachidonic acid (IC50=2.6±0.24 μmol/L); 2) displaced SQ29,548 from its binding sites on platelets; 3) lacked any detectable effects on aggregation stimulated by ADP, or the thrombin receptor activating-peptide 4; 4) blocked calcium mobilization induced by U46619, but not by ADP; and 5) failed to raise cAMP levels. Conclusion: The findings indicate that glybenclamide exerts inhibitory effects on platelets by interacting with TPR. Thus, glybenclamide or a rationally designed derivative has the potential to serve as an antithrombotic agent.